Bibliometric Mapping of Islamic Law Research: Global Perspectives and Scholarly Networks (2000-2025) - Judijanto, Loso; Muhammadong, Muhammadong (West Science Islamic Studies, 2025)
This study presents a comprehensive bibliometric analysis of Islamic law research published globally between 2000 and 2025, using VOSviewer as the primary analytical tool. Drawing on data from the Scopus database, the study examines 25 years of scholarly output to identify leading authors, institutional collaborations, thematic trends, and geographic distributions. The co-authorship network reveals several dominant scholarly clusters, notably those led by Wael B. Hallaq and Mohammad Hashim Kamali, indicating vibrant discourse across traditional, reformist, and applied legal thought. Country collaboration analysis highlights Indonesia’s central role in global Islamic law research, signaling a shift toward Southeast Asian academic leadership. Keyword co-occurrence and temporal mapping show a thematic transition from classical jurisprudential subjects such as fiqh and sharia toward more contemporary issues like human rights, Islamic finance, family law, and maqasid al-shariah. The density visualization further reveals underexplored topics with potential for future research. This study contributes to the meta-knowledge of Islamic legal scholarship by offering a structured overview of its evolution, fragmentation, and global reach, while identifying emerging directions for interdisciplinary engagement.